Electric toothbrush for biofilm control in individuals with Down syndrome: a crossover randomized clinical trial - Aryvelto Miranda SILVA; Luís Fernando Bandeira MIRANDA; Ana Sara Matos ARAÚJO; Raimundo Rosendo PRADO JÚNIOR; Regina Ferraz MENDES (Sociedade Brasileira de Pesquisa Odontológica, 2020)
Abstract Poor oral hygiene seems to be the norm in children and teenagers with Down Syndrome (DS). Advances in design and types of toothbrushes may improve biofilm control. This randomized, single-blind, crossover clinical trial evaluated the effectiveness of electric toothbrushes regarding mechanical control of biofilm in children and teenagers with DS and their cooperation. Twenty-nine participants with DS, aged 6 to 14 years, used both types of toothbrushes: electric (ET) and manual (MT). The order of use of the different types of toothbrushes was randomly defined, including a 7-day period with each type with 7-day washout period in between. The Turesky-Quigley-Hein biofilm index was used before and after brushing to assess the effectiveness of the technique. Frankl's behavioral scale was used during toothbrushing to assess the participants' cooperation. Paired T-test, Mann Whitney, Chi-square, and Fisher's Exact tests were applied, with a significance level of 5%. The quantity of dental biofilm was significantly reduced after both brushing techniques (p < 0.001). However, no significant difference was found in total biofilm (ET: 0.73 ± 0.36; MT: 0.73 ± 0.34; p = 0.985) or % biofilm reduction (ET: 72.22%; MT: 70.96%; p = 0.762) after brushing between techniques or in % biofilm reduction between toothbrushes of age groups (6 -9 years, p = 0.919; 10-14 years, p = 0.671). Participants showed similar cooperation level with the two types of toothbrush (p = 1.000). The use of electric or manual toothbrush had no effect on the quantity of dental biofilm removed in children and teenagers with DS, nor did it influence their cooperation during the procedure.